Optometry Profession Practice Control - Sompochpisut, Pisut; Umpai, Kiarttiporn (Rajapark Journal, 2020)
At present, Thailand has a wide range of practice of optometry. However, in Thailand, there is no law to control the practice of optometry, whether it is a process to enter the profession to determine the qualifications, basic knowledge of those who will practice, and consider allowing the practice of optometry in accordance with the professional ethics standards, measures to enforce the practice of optometry by the specified conditions. Including penalties for those who practice of optometry without permission. Resulting in people who do not have the knowledge and ability in optometry to practice optometry as a result, the current profession of vision is not ethical standards which may cause damage to clients. Therefore, this research has been conducted to study the necessity of establishing legal measures to control the practice of optometry with the study of facts (Non-Doctrinal Legal Research) to know the problem, the fact that the profession of professional vision is a professional and considered a profession that requires professional supervision or not. After being aware of the facts, then studying the Doctrinal Legal Research by conducting a comparative study with foreign laws relating to the practice of optometry lead to proposals to regulate the profession of perspective measurement by law by stipulating conditions for professional practice Measures to enforce compliance with the law, including criminal penalties for violations.